The Lenient Sentencing of Corruptors from the Perspective of the Judicial Power - Nurrohim, Hamdan (Yayasan Sinergi Kawula Muda, 2023)
The conditional sentences for corruptors are considered too lenient and not in line with the law. However, judges have the freedom to choose the type of punishment and sentencing that suits their discretion because, in the positive criminal law principles in Indonesia, there is the use of alternative criminal sanctions alongside the adoption of a minimum, maximum general, and maximum specific criminal system within each criminal offense. This study is dissected using juridical-normative analysis based on the law. Its aim is to provide criticism of the rationale in deciding a case, thereby ensuring a sense of justice is fulfilled.